2019
DOI: 10.1002/pits.22238
|View full text |Cite
|
Sign up to set email alerts
|

The impact of teacher–student relationships and classroom engagement on student growth percentiles of 7th and 8th grade students

Abstract: The study examined the extent that teacher–student relationships (TSR) influenced basic psychological needs, engagement, and student growth using the self‐systems process model as a framework using structural equation modeling. Based on prior research, it was hypothesized that context (TSR) influenced self (basic psychological needs), which influenced action (engagement), and consequently, influenced outcome (student score and grade point average‐GPA). The findings of the study supported prior research that a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The quality of teacherlearner interpersonal relationships can affect some positive psychological constructs, including academic engagement, foreign language enjoyment, resilience, grit, self-efficacy, and wellbeing among learners in order to improve learners' healthy behavioral functioning (Derakhshan, 2021). Concerning learners' academic engagement, Dennie et al (2019) found that teacherlearner interpersonal relationships significantly affected learners' academic engagement in educational contexts. They argued that teacher-learner interpersonal relationship positively affects learners' emotional requirements, which influence academic engagement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The quality of teacherlearner interpersonal relationships can affect some positive psychological constructs, including academic engagement, foreign language enjoyment, resilience, grit, self-efficacy, and wellbeing among learners in order to improve learners' healthy behavioral functioning (Derakhshan, 2021). Concerning learners' academic engagement, Dennie et al (2019) found that teacherlearner interpersonal relationships significantly affected learners' academic engagement in educational contexts. They argued that teacher-learner interpersonal relationship positively affects learners' emotional requirements, which influence academic engagement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given the fact that teacher-student rapport lies at the heart of education (Xie and Derakhshan, 2021), considerable attention has been devoted to its positive educational outcomes (Roorda et al, 2011;Opdenakker et al, 2012;Lucas-Molina et al, 2015;Ma et al, 2018;Dennie et al, 2019;Meng, 2021; to cite a few). Nonetheless, the positive effects of this communication behavior on students' well-being have not been widely studied (Holfve-Sabel, 2014;Graham et al, 2016).…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Since the grades are not normally distributed and the estimates of the first and last grades are highly unstable, the use of traditional linear regression models is not suitable for this. As the developer of the SGP model, Betebenner innovatively used the method of quantile regression to obtain the SGP value [18]. Since the conditional quantile of dependent variables is affected by independent variables, quantile regression can more accurately describe the variation range of independent variables to dependent variables and the shape of the conditional distribution and accurately capture the data characteristics at both ends of the distribution to obtain more comprehensive data analysis.…”
Section: Mathematical Basis Of Sgp Model Designmentioning
confidence: 99%